Analisis Kesalahan Ejaan Pada Teks Eksposisi Siswa Kelas V Sekolah Dasar Persatuan Umat Islam Haurgeulis - Siti Af’idatul Insyiroh; Moch. Hasyim Fanirin; Dewi Utami (Jurnal Pendidikan Indonesia, 2022)
The importance of using good and correct language rules needs to be trained and applied from an early age in elementary schools and madrasah Ibtidaiyah thus there are no errors or mistakes in language. Elementary school students are guided to be able to understand spelling rules following the General Guidelines for Indonesian Spelling (PUEBI) in language skills, one of which is writing skills. They can provide information in their writings correctly thus the readers can understand the message or opinion conveyed easily.Researchers focus on two scopes, namely; the mistakes of fifth graders of SD PUI Haurgeulis In using capital letters, the punctuation marks and commas, the use of words in expository essays, and their understanding of Indonesian spelling.This study is used the descriptive qualitative method. For the data collection, researchers conducted observations, interviews, and documentation. At the data analysis stage, the researchers reduce the data, encode, present, and finally find conclusions from the processed data. The result of this study indicates that students quite understand spelling in Indonesian properly and correctly. The students' errors in the use of spelling are as follows; as many as 156 capital letter errors occupy the number 67%, as many as 26 punctuation errors occupy the number 22%, then the last as many as 51 errors in word usage occupy the number 11%, and all included in the overall percentage error diagram contained in the essays of class students V SD PUI Haurgeulis.